Molecular Insights and Bioactive Spectrum of Vaccinium cyanococcus: Exploring its Role in Redox Balance, Immune Response, and Glucose Homeostasis - Shafia Arshad; Aisha Sethi; Rida Siddique; Usman Wajid; Amina Riaz; Maryam Zain; Farah Zafar; Asia Perveen; Faiza Irshad; Hafiz Muhammad Arsalan; Neelam Farheen (Biomedical and Biotechnology Research Journal)
Background: Vaccinium cyanococcus (blueberries) is a perennial fruit from the Ericaceae family, and Vaccinium genus is recognized for its diverse health benefits largely due to their rich content of antioxidants, particularly anthocyanins and other polyphenols. This study aims to explore the phytochemical composition, biological activities, and in silico perspectives of blueberry extracts. Methods: Methanolic and ethanolic extracts were prepared, and their antioxidant, anti-inflammatory, and antidiabetic properties were evaluated using standard assays. Results: Phytochemical screening revealed the presence of anthocyanins, flavonoids, phenols, and saponins in both extracts, with methanol showing higher efficiency in extracting bioactive compounds. Gas chromatography–mass spectrometry analysis identified various biologically active compounds, including 2-Isopropoxyethyl propionate, 3-Quinolinecarboxylic acid, and 7-Oxodehydroabietic acid, which possess antioxidant and anti-inflammatory properties. The methanolic extract exhibited the highest antioxidant potential (85% inhibition at 0.9 mg/mL) and anti-inflammatory activity (90% inhibition at 0.9 mg/mL). In silico docking studies further confirmed the binding affinity of imidazole and 2-Chloro-5-cyanophenylboronic acid to the 2X8Y protein, suggesting their potential for drug development. Conclusions: The study demonstrates that blueberry extracts hold significant therapeutic potential, particularly in the management of oxidative stress, inflammation, and diabetes. While methanolic extract performed better than ethanolic extract, further clinical studies are necessary to validate these findings and determine optimal dosages for disease management.